Struktur Lirik Lagu dalam Album Cidro Asmoro Kajian Strukturalisme - Nurkhayatun, Umi; Mardiyansyah, Mardiyansyah; Werdiningsih, Yuli Kurniati (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2022)
This research was written with the aim to determine the lyric structure of the song in the album Cidro Asmoro using the study of Structuralism. The structure in the lyrics of this song consists of physical structure and inner structure. Physical structure is the structure of the builder of a poem that is physical or fit in the form of word order. While the inner structure is the structure of the poet builder from within or contains the meaning that the author wants to express. The research method used to analyze the physical structure and the inner structure uses a qualitative descriptive method. The data used in this study are words, phrases, and sentences in the lyrics of the song Cidro Asmoro that refer to the structure of the builder. The results found in this study is that there is a physical structure in the form of majas, recitation, diction, concrete words and rhyme in the lyrics of songs in the album Cidro Asmoro. Majas or language styles found include majas personification, metaphor, association, allegory and hyperbole. In addition, also found imagery or imagery in the form of imagery of sight, hearing, taste, touch and movement. The inner structure in the lyrics of Cidro Asmoro's album has themes, tastes, tones and messages. Selection of lyrics and words from Cidro Asmoro's album has a unique characteristic to convey the feelings experienced by the author. This feeling can be from love, disappointment, confusion, anger and even enthusiasm. Cidro Asmoro's album contains the story of a man's love struggle who ultimately has to give up his lover with another man.